ANALISIS PENGUJIAN STRUKTUR BALOK LAMINASI KAYU SENGON DAN KAYU KELAPA - Sri Handayani (Jurnal Teknik Sipil dan Perencanaan)
Wood Sengon (Sengon) is a type of timber that can quickly grow, accessible but its use as a construction material has not been optimized. The technology used to support the wood as a construction material is a laminate. Engineering experiments was done by making laminated beams of wood Sengon and wood coconut. The purpose of this study is to determine how much the increase in flexural strength for laminated wood Sengon beams and wood Coconut beams as a replacement of structural beam with a variety of adhesive and timber placement. The method used is an experimental method for flexural strength testing of laminated beams. The results showed an average flexural strength of the maximum obtained in laminated beams with variations EP-S (adhesive epoxy glue and placement position in the wood Sengon) amounted to 679 350 kg / cm2. An increase in the strength of 254 025 kg / cm2 (59.72%) are from wood Sengon bending strength 425 325 kg / cm2 (probe grade IV) to 679 350 kg / cm2 (strong class III). The use of technology should pay attention to the position of the bearing laminated wood. Wood with strong higher class should be put on the outside position to provide reinforcement for the wood with a powerful low grade placed in the position.